Inhibition of intestinal tumor formation by deletion of the DNA methyltransferase 3a - Weis, Britta; Schmidt, J.; Maamar, H.; Raj, A.; Lin, H.; Tóth, Csaba; Riedmann, K.; Raddatz, G.; Seitz, Helmut K.; Ho, Anthony Dick; Lyko, F.; Linhart, Heinz (Oncogene, 2015)
Aberrant de novo methylation of DNA is considered an important mediator of tumorigenesis. To investigate the role of de novo DNA methyltransferase 3a (Dnmt3a) in intestinal tumor development, we analyzed the expression of Dnmt3a in murine colon crypts, murine colon adenomas and human colorectal cancer using RNA fluorescence in situ hybridization (FISH), quantitative PCR and immunostaining. Following conditional deletion of Dnmt3a in the colon of APC(Min/+) mice, we analyzed tumor numbers, genotype of macroadenomas and laser dissected microadenomas, global and regional DNA methylation and gene expression. Our results showed increased Dnmt3a expression in colon adenomas of APC(Min/+) mice and human colorectal cancer samples when compared with control tissue. Interestingly, in tumor tissue, RNA FISH analysis showed highest Dnmt3a expression in Lgr5-positive stem/progenitor cells. Deletion of Dnmt3a in APC(Min/+) mice reduced colon tumor numbers by ~40%. Remaining adenomas and microadenomas almost exclusively contained the non-recombined Dnmt3a allele; no tumors composed of the inactivated Dnmt3a allele were detected. DNA methylation was reduced at the Oct4, Nanog, Tff2 and Cdkn1c promoters and expression of the tumor-suppressor genes Tff2 and Cdkn1c was increased. In conclusion, our results show that Dnmt3a is predominantly expressed in the stem/progenitor cell compartment of tumors and that deletion of Dnmt3a inhibits the earliest stages of intestinal tumor development.
published online 19 May 2014
Gesehen am 29.06.2020